A Systematic Review of Clinical Studies Investigating Mesenchymal Stem Cells for Fracture Non-Union and Bone Defects - Killington, Kieran; Mafi, Reza; Mafi, Pouya; Khan, Wasim S. (Current Stem Cell Research & Therapy, 2018)
Background: Fracture non-union is a significant problem with a wide range demographic and massive socioeconomic elements, as well as the clinical difficulties it presents. Conventional treatments with autograft and allograft bone grafting pose serious difficulties, thus, it is necessary to develop novel techniques with our ever increasing knowledge of bioengineering using natural materials. Objective: To search for current evidence regarding the treatment of fracture non-union or bone defects using mesenchymal stem cells (MSCs). Results: The results presented in this review show that the use of mesenchymal stem cells for the treatment of non-union and bone defects is optimistic. Several papers had positive outcomes to report. There is a need for higher level evidence. Conclusion: A strong need of clinical results is required to further progress in cell therapy. Launched trials will hopefully provide this information in the near future. If clinical trials are positive, further development of complex tissue engineering techniques may be developed to treat large bone defects.
Keywords: Bone defects